Characterization of marine-derived halogenated indoles as ligands of the aryl hydrocarbon receptor. (2022) - King, Jessie; Woolner, Victoria H.; Keyzers, Robert A.; Rosengren, Rhonda J.
Abstract: The aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor thought to mediate a number of physiological roles in the body, is becoming a target of interest for the development of new therapeutics. However, previous research has demonstrated that the downstream effects of AhR ligands cannot be predicted based simply on whether a ligand acts as an agonist or antagonist and the persistence of AhR signaling is thought to be a key determining feature. The current study investigated the AhR activity of four halogenated indoles isolated from the New Zealand red alga, Rhodophyllis membranacea : 4, 7-dibromo-2, 3-dichloroindole (4DBDCI), 7-bromo-2, 3-dichloro-6-iodoindole (BDCII), 6, 7-dibromo-2, 3-dichloroindole (6DBDCI) and 2, 6, 7-tribromo-3-chloroindole (TBCI). Their ability to activate AhR signaling, measured as CYP1A1 activity via the ethoxyresorufin O -deethylase (EROD) assay, was determined in human HepG2, mouse Hepa1c1c7 and rat H4IIE liver cancer cells. All four compounds induced CYP1A1 activity in HepG2 cells, suggesting they all acted as AhR agonizts. 4DBDCI was particularly efficacious, inducing an 11-fold increase. Hepa1c1c7 and H4IIE cells, however, were generally less responsive to the halogenated indoles. All four compounds were persistent AhR agonizts, inducing peak CYP1A1 activity after 72 h. Moreover, the 2, 3, 6, 7-substituted BDCII, 6DBDCI and TBCI, but not 4DBDCI, competed with 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) for AhR binding as observed by the inhibition of TCDD-induced CYP1A1 activity. Overall, the current study has characterized four previously untested AhR ligands, highlighting differences in species sensitivity and persistence of signaling to provide a framework for their potential future use. Graphical Abstract: ga1 Highlights: Four halogenated indoles derived from algae have been found to activate the AhR. Human, mouse and rat cell lines show different sensitivity to these AhR ligands. EROD assays were used to highlight persistent vs transient AhR activation. All four compounds produced persistent effects.